Investors' international law - Sattorova, Mavluda; Ho, Jean (London [England] : Hart Publishing, 2021)
"International investment law is at the edge of crisis. After nearly a century of being a trusty amulet for investor protection from States, it is currently facing growing criticisms for its failure to address corruption, abuse, environmental damage, and other forms of investor misconduct. Policymakers, legal practitioners and civil society groups are increasingly calling for the dismantling or rewriting of the international law governing investors. Reform initiatives range from the rejection of international law as a governing regime for investors, to the dramatic overhaul of investment treaties that supposedly enable investor overprotection, to the creation of a multilateral international instrument that would enable the litigation of claims against errant businesses before an international tribunal. Whether these initiatives succeed in disciplining investors remains to be seen. What these initiatives undeniably show however, is that change is warranted to counteract this lopsided investors' international law. Despite the growing body of literature on the topic of investor accountability, broader and more profound issues of substantive rules on and regimes governing investor obligations and responsibilities remain underexplored. It is this gap in the literature that this collection seeks to narrow by offering a fresh, book-length analysis of investor accountability under general and customary international law, international human rights law, international environmental law, international humanitarian law, as well as international investment law. Each chapter in the book addresses a different and underexplored dimension of investor accountability, thus offering a novel and consolidated study of international law. This book will be of immense assistance to legal practitioners, academics and policy makers involved in the design, drafting, application and reform of various international instruments addressing investor accountability."--
Introduction - Jean Ho & Mavluda Sattorova -- PART 1: A SHIFT IN EMPHASIS FROM INVESTOR PROTECTION TO INVESTOR ACCOUNTABILITY -- 1.International Law's Opportunities for Investor Accountability - Jean Ho -- PART 2: SOURCING DIFFERENT INVESTOR OBLIGATIONS -- 2.Investor obligations to do good: harnessing investment for socially inclusive development- Mavluda Sattorova -- 3.Corruption as an International Wrong - Jackson Shaw Kern -- 4.Crafting Enforceable Environmental Obligations for Investors - Priscilla Pereira de Andrade & Nitish Monebhurrun -- 5.Investor Obligations and Responsibility Amid Armed Conflict - Jure Zrilic -- 6.International Investment Law and Local Communities: Is There a Way Forward? - Lorenzo Cotula & Nicolás Perrone -- 7.Investor Obligations in Investment Treaties: Missing Text or a Matter of Application? - Prabhash Ranjan -- PART 3: ISSUES IN CORPORATE INVESTOR OBLIGATIONS AND ACCOUNTABILITY -- 8.The Role of Corporate Soft Law Responsibilities in Defining Investor Obligations in International Investment Agreement - Barnali Choudhury -- 9.Risk Distribution in International Law: Corporate Legal Form and Investment Law as Tools of Risk Avoidance- Anil Yilmaz Vastardis -- 10.Applying International Humanitarian Law to Corporations: Lessons from the United States - Julian Ku -- PART 4: THE INSTITUTION OF INVESTOR ACCOUNTABILITY -- 11.Reprisals Against Illegal Investments- Martin Andrew Jarrett -- 12.Investor Obligations in Counterclaims Before Investor-State Tribunals- Tomoko Ishikawa -- 13.Sword and Shield? The Role of International Law in Transnational Corporate Responsibility Litigation- Andrew Sanger -- 14.Conclusion - Surya Deva.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Investments, Foreign (International law); Investments, Foreign -- Law and legislation; Investments -- Moral and ethical aspects; International economic & trade law; Electronic books